Pengaruh Pemesinan Milling Terhadap Kekasaran Permukaan Baja Tahan Karat Martensitik Modifikasi Aisi 410 3Mo – 3Ni dan Keausan Material Cutter End Mill [Effect of Milling Machining on Surface Roughness of AISI 410 3Mo-3Ni Martensitic Stainless Steel and W - Anwar, Moch. Syaiful; Nugroho, Hady Zhakwan; Wiyono, Slamet; Mabruri, Efendi (Jurnal Metalurgi, 2018)
Process of machining always occurs interaction between cutting tool and workpiece causing chisel or cutting knife experience friction and wear. The purpose of this research is to observe the effect of spindle speed and feed rate on surface roughness of martensitic stainless steel modified AISI 410 3Mo-3Ni and wear of cutter end mill. The method of variance analysis is used in the analysis of machining results. The result of this research is the smallest surface roughness value obtained at 1300 rpm of spindle speed cutting and 190 mm/min of feed rate. The largest surface roughness value obtained on 950 rpm of spindle speed and 760 mm/menit of feed rate. Then, the smallest wear value of edge of cutter endmill of 40.16 μm is found on spindle speed variation of 950 rpm and feed rate 190 mm/min and the largest wear value of edge of cutter end mill of 255.23 μm is found on spindle speed variation of 1300 rpm and feed rate 760 mm/min